Socialism, Capitalism, and the COVID-19 Epidemic: Interview with Victor Wallis. Issue 2 (2nd April 2020) - Wallis, Victor; Zhuo, Mingliang
ABSTRACT: In the context of coronavirus raging around the world, in April 2020 Dr. Mingliang Zhuo interviewed Prof. Victor Wallis, former editor of Socialism and Democracy, on some important issues via email. Wallis points out in the exclusive interview that the US response to the pandemic has triggered a disastrous economic depression. The United States has not done well in dealing with the epidemic. However, China, Cuba, and other countries applying socialist principles have done well by achieving a combination of administrative decrees and popular initiatives and participation. The quality of universal services would be more dependably assured within a fully socialist framework.